The resilience of short food supply chains during the COVID-19 pandemic: a case study of a direct purchasing network - Ušča, Maija; Tisenkopfs, Talis (Frontiers in Sustainable Food Systems, 2023)
Introduction The COVID-19 pandemic has presented challenges to global food supply chains. Since the beginning of the pandemic researchers have studied various food supply chain issues influenced by the COVID-19 crisis, including impacts on consumer behavior, and logistical and organizational changes to food supply chains. Despite the proliferation of studies on food supply chains during the pandemic, only a few researchers have focused on short food supply chains and their resilience. Therefore, the aim of this study was to explore the resilience of short food supply chains during the COVID-19 pandemic using a direct purchasing (DP) network as a case study. The study considered three research questions. (1) How has the functioning of the DP network changed during the COVID-19 pandemic? (2) What role do resilience elements (i.e., readiness to shocks, responsiveness to disruption, and recovery from the crisis) play in the short food supply chain response to the COVID-19 crisis? (3) Which innovations in the short food supply chain would further the recovery process, and thus resilience, after the crisis? Methods This article presents a case study of a direct organic food purchasing network in Latvia. The analysis of economic data regarding the dynamics of organic product demand and supply in the DP network was supplemented with an analysis of qualitative data gathered through semi-structured in-depth interviews with representatives of three groups of DP network participants: consumers, producers, and DP network organizers. Results and discussion From the consumer and producer experiences, the DP network was a flexible short food chain that could adapt quickly in a crisis. While the number of DP distribution points and total number of purchases decreased during the pandemic, a statistically significant increase in the number of product units sold compared to the pre-COVID-19 period was observed. From the perspective of food chain resilience elements, the reactive strategies of the DP network as a short food supply chain were highlighted. During the COVID-19 pandemic, the organizational and product innovations introduced in the DP network played a key role in enhancing the resilience of the short supply chain in the context of the wider food system.